A Analysis of Gunshot Sensors and Buzzers on Bulletproof Vests in Real Time Based on Internet of Things (IoT) - Jeffri Kurniawan; Muhamad Risal Duwila; Dekki Widiatmoko (International Research & Development for Human Beings (IRDH), 2025)
This research develops a prototype of an Internet of Things-based bulletproof vest that can monitor heart rate and detect gunshots in real time. The test results show that the shot impact sensor has a detection accuracy of 98.5%, the installed heart rate sensor has a sensitivity of 96%, and a notch condition detection accuracy of 95%. The recorded data sending time to the web server was 5.936 seconds, with an average waiting time between 5.5 and 6.3 seconds. Once a dangerous condition is detected, a sound notification will be sent via the buzzer within 0.7 seconds. Overall, this system provides accurate and efficient information on personnel conditions, which is expected to assist in faster tactical responses in field situations